Social Embeddedness as a Business Goal: New Theoretical Implications from the Case of a Global Value Chain - Belyavskiy, Boris (Journal of Economic Sociology, 2020)
This paper provides new theoretical implications for the concept of social embeddedness as one of the main objectives for business relations. Previous studies have considered social embeddedness as an external factor to market exchanges that forms outside of economic relations; in other words, embeddedness appears as an incidental product of market interactions. Here, I propose that social embeddedness is being intentionally constructed by market actors as an integral part of a business process. This view is developed by a theoretical adaptation of studies in relational marketing and the sociology of valuation. Relational marketing shows that interfirm relations have additional value for businesses and can educate market practitioners to intensify social interactions. Valuation studies explain the process of value creation for end goods, and this explanation is applied to interpreting the value of interfirm relations. For the empirical validation, I focus on the field of global value chains because the global coordination of business interactions requires an explicit discussion of relational characteristics. The research is performed using a qualitative design. The empirical part consists of 13 months of participant observation as a sales manager in a Russian global value chain that works in fast-moving consumer goods and consumer electronics. Also, 33 deep semistructured interviews were conducted with employees of the global value chain. Data analysis is performed within a grounded theory perspective. The empirical section demonstrates that the proposed vision of embeddedness as an integral and desirable part of a business process is applicable to firm practices. Economic actors participate in permanent valuation processes to maintain a common interpretation of interfirm relations; they conceptualize business ties as an important source of market value.